1997
DOI: 10.1093/humrep/12.3.457
|View full text |Cite
|
Sign up to set email alerts
|

Responsiveness of human male volunteers to immunization with ovine follicle stimulating hormone vaccine: results of a pilot study

Abstract: A study of 140 days duration was performed to examine if human male volunteers (n = 5) respond to ovine follicle stimulating hormone (oFSH) immunization (administered adsorbed on Alugel on days 1, 20, 40 and 70) by producing antibodies capable of both binding and neutralizing bioactivity of human FSH. The kinetics of antibody production for both the immunogen (oFSH) and the cross-reactive antigen (hFSH) were essentially similar. The volunteers responded only to the first two immunizations. The boosters given o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
4

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 15 publications
1
36
0
4
Order By: Relevance
“…37 While there are studies showing that immunization of monkeys for FSH or FSHR brings about azoospermia, 38,39 the bulk of evidence shows that the FSH dependence of monkey spermatogenesis is very similar to that of other mammalian species, i.e. FSH is not essential, although it synergizes with T to maximize sperm output.…”
Section: Rodentsmentioning
confidence: 99%
“…37 While there are studies showing that immunization of monkeys for FSH or FSHR brings about azoospermia, 38,39 the bulk of evidence shows that the FSH dependence of monkey spermatogenesis is very similar to that of other mammalian species, i.e. FSH is not essential, although it synergizes with T to maximize sperm output.…”
Section: Rodentsmentioning
confidence: 99%
“…Normal function of the gondotrophic axis, especially normal FSH secretion, plays crucial roles in spermatogenesis [20] [21]. Several experimental and clinical studies have demonstrated the importance of FSH in regulating a normal quantitative spermatogenic process in animals and humans [22] [23]. It has also been suggested that high serum FSH levels is intimately related to a decrease of spermatogenesis function.…”
Section: Discussionmentioning
confidence: 99%
“…Блокада рецепторов к ФСГ у взрос-лых макак-резусов приводит к бесплодию. Био-нейтрализация циркулирующего человеческого ФСГ снижает качество и количество сперматозо-идов [10].…”
Section: урологические ведомостиunclassified